Individual differences in emotion-cognition interactions: emotional valence interacts with serotonin transporter genotype to influence brain systems involved in emotional reactivity and cognitive control - Stollstorff, Melanie; Munakata, Yuko; Jensen, Arielle P.; Guild, Ryan M.; Smolker, Harry R.; Devaney, Joseph M.; Banich, Marie T. (Frontiers in Human Neuroscience, 2013)
The serotonin transporter gene (5-HTTLPR) influences emotional reactivity and attentional bias towards or away from emotional stimuli and has been implicated in psychopathological states, such as depression and anxiety disorder. The short allele is associated with increased reactivity and attention towards negatively-valenced emotional information, whereas the long allele is associated with that towards positively-valenced emotional information. The neural basis for individual differences in the ability to exert cognitive control over these bottom-up biases in emotional reactivity and attention is unknown, an issue investigated in the present study. Two groups, homozygous 5-HTTLPR long allele carriers or homozygous short allele carriers, underwent functional magnetic resonance imaging (fMRI) while completing an Emotional Stroop-like task that varied with regards to the congruency of task-relevant and task-irrelevant information and the emotional valence of the task-irrelevant information. Behaviorally, participants demonstrated the classic “Stroop effect” (slower responses for incongruent than congruent trials), which did not differ by 5-HTTLPR genotype. However, fMRI results revealed that genotype influenced the degree to which neural systems were engaged depending on the valence of the conflicting task-irrelevant information. While the “Long” group recruited prefrontal control regions and superior temporal sulcus during conflict when task-irrelevant information was positively-valenced, the "Short" group recruited these regions when task-irrelevant information was negatively-valenced. Thus, participants successfully engaged cognitive control to overcome conflict in an emotional context using similar neural circuitry, but the engagement of this circuitry depended on emotional valence and 5-HTTLPR status. These results suggest that the interplay between emotion and cognition is modulated, in part, by a genetic polymorphism that influences serotonin neurotransmission.